PERAN BUMDES DALAM PENGELOLAAN SUMBER DAYA ALAM DAN KEUANGAN DESA: STUDI KASUS PADA DESA SOPURAA, KABUPATEN KOLAKA - Anshar, Anshar; A. Musyarrafah Vetriyani; Andi Zulkarnain; Abd.Haris (Cahaya Ilmu Bangsa, 2025)
This research aims to examine the role of Village-Owned Enterprises (Bumdes) in managing natural resources and village finances, in Sopuraa Village, Kolaka Regency. Sopuraa Village has significant natural resource potential, especially in the nickel mining sector, which is one of the main sources of income for the village. Bumdes in this village plays a role in managing these natural resources, as well as in managing village finances which originate from mining products. This research uses a qualitative approach with a case study method, where data is collected through in-depth interviews, observations and document analysis involving Bumdes administrators, village officials, the community and related parties in the mining sector. The research results show that Bumdes plays a role in facilitating the management and utilization of nickel mining products for village development and improving community welfare. However, the management of nickel IUPs carried out by Bumdes faces several challenges, such as a lack of technical capacity and effective supervision. Apart from that, village financial management is also faced with the risk of dependence on the mining sector which tends to fluctuate. This research recommends the need to increase managerial capacity and strengthen sustainable planning in managing the potential of natural resources and village finances in the future.